Jaya optimization algorithm implemented on a new novel design of 6-DOF AUV body: a case study - Basil, Noorulden; Marhoon, Hamzah M.; Gokulakrishnan, S.; Buddhi, Dharam (Multimedia tools and applications, 2025)
The novel Jaya Optimization Algorithm (JOA) was utilized in this research to evaluate the efficiency of a new novel design of Autonomous Underwater Vehicle (AUV). The Three Proportional Integral Derivative (PID) controllers were used to obtain the optimum output for the AUV Trajectory, which can be considered as a main side of the research for solving the AUV Performance. The optimization technique has been developed to solving the motion model of the AUV in order to reduce the rotations of trajectory for the AUV 6-DOF Body in the axis’s in x, y and z for the overall positions, velocity were measured in 50 seconds as the velocity compared with the simulated time, and to execute the optimum output for the dynamic kinematics model based on the Novel Euler-6 DOF AUV Body Equation implemented on MATLAB R2021a Version.